Role of Polytechnics in Environmental Protection and Sustainable Development - Ramakrishna Sastri, C. (Journal of Engineering Education Transformations, 1994)
This article is an extract of a paper on the same topic presented at the NATIONAL SEMINAR ON ENVIRONMENTAL ENGINEERING held at T. T. T. I., Madras on 4th March 1994. The article reviews how in the guise of development and progress, environmental degradation and pollution have already reached alarming proportions in most developing countries especially in urban conglomerations, compounded by problems of population explosion and migration. The task of crying a halt to this process and limiting pollution levels to acceptable standards has become a stupendous task impossible to tackle by designated government agencies and departments alone. Educational institutions at all levels need to get involved and introduce in their courses relevant components of environmental awareness, basic knowledge, skills and attitudes in order to produce a future gene ration of citizens who can help fight this degradation and pollution. Polytechnics in particular, could do a lot more in this area. They could produce environmentally conscious technicians to avoid repetition of the infamous Bhopal and Chernobyl type of disasters. They could also take Lip environment - friendly activities by acquiring a GREEN lable and produce local pressure groups to resist and fight all types of damaging activities with in their own communities, besides teaching courses related to environmental engineering. This article elaborates the above concepts with practicable and implementable strategies.